Humanism as the Theme of Chinese Modernity - Hui, Wang (Surfaces, 1995)
By examining humanist and Enlightenment discourse in reference to China and to the West, this essay reopens the question of how modern Chinese intellectuals assimilated Western ideas and applied them in their own social practice. It indicates the historical conceptions that underlie Western humanism and traces the evolution of Chinese humanist discourses in terms of their media of dissemination, their impact on the organization of knowledge, and their relationship to Marxist concepts of the mode of production.